Multi-Scale Simulation of the Simian Immunodeficiency Virus Fusion Peptide - Crowet, Jean-Marc; Parton, Daniel L; Hall, Benjamin A; Steinhauer, Sven; Brasseur, Robert; Lins, Laurence; Sansom, Mark S. P (The journal of physical chemistry. B, 2012)
Fusion peptides of type I fusion glycoproteins are structural elements of several enveloped viruses which enable the fusion between host and virus membranes. It is generally suggested that these peptides can promote the early fusion steps by inducing membrane curvature and that they adopt a tilted helical conformation in membranes. Although this property has been the subject of several experimental and in silico studies, an extensive sampling of the membrane peptide interaction has not yet been done. In this study, we performed coarse-grained molecular dynamic simulations in which the lipid bilayer self-assembles around the peptide. The simulations indicate that the SIV fusion peptide can adopt two different orientations in a DPPC bilayer, a major population which adopts a tilted interfacial orientation and a minor population which is perpendicular to the bilayer. The simulations also indicate that for the SIV mutant that does not induce fusion in vitro the tilt is abolished.